Recent Methods for the Synthesis of Noble‐Metal‐Free Hydrogen‐Evolution Electrocatalysts: From Nanoscale to Sub‐nanoscale. Issue 6 (16th May 2017) - Wang, Jiong; Zhang, Hua; Wang, Xin
Abstract : Electrochemical splitting of water into hydrogen is a promising approach for energy conversion and storage. The development of efficient and low‐cost electrocatalysts is crucial for realizing the wide application of this technology. Here, recent advances in the synthesis of various electrocatalytic structures toward the hydrogen‐evolution reaction (HER) are summarized, centering on several important examples of nonprecious‐metal nanostructures, molecular clusters, and single‐atomic/molecular catalysts. The central strategy to achieve high electrocatalytic activity is discussed, namely, maximizing the utilization efficiency of all active sites through downsizing and merging the gap between homogeneous and heterogeneous catalysis. To close, the current challenges and future opportunities are discussed. Abstract : Recent advances in the synthesis of electrocatalytic structures toward the hydrogen‐evolution reaction, including nonprecious‐metal nanostructures, molecular clusters, and single‐atomic or molecular catalysts are highlighted. The central strategy to achieve high electrocatalytic activity is discussed; namely, maximizing the utilization efficiency of all active sites through downsizing and merging the gap between homogeneous and heterogeneous catalysis.